Upregulation of PGC-1α expression by Alzheimer's disease-associated pathway: presenilin 1/amyloid precursor protein (APP)/intracellular domain of APP - Robinson, Ari; Grösgen, Sven; Mett, Janine; Zimmer, Valerie C.; Haupenthal, Viola J.; Hundsdörfer, Benjamin; Stahlmann, Christoph P.; Slobodskoy, Yulia; Müller, Ulrike C.; Hartmann, Tobias; Stein, Reuven; Grimm, Marcus O. W. (Aging cell, 2014)
Cleavage of amyloid precursor protein (APP) by β- and γ-secretase generates amyloid-β (Aβ) and APP intracellular domain (AICD) peptides. Presenilin (PS) 1 or 2 is the catalytic component of the γ-secretase complex. Mitochondrial dysfunction is an established phenomenon in Alzheimer's disease (AD), but the causes and role of PS1, APP, and APP's cleavage products in this process are largely unknown. We studied the effect of these AD-associated molecules on mitochondrial features. Using cells deficient in PSs expression, expressing human wild-type PS1, or PS1 familial AD (FAD) mutants, we found that PS1 affects mitochondrial energy metabolism (ATP levels and oxygen consumption) and expression of mitochondrial proteins. These effects were associated with enhanced expression of the mitochondrial master transcriptional coactivator PGC-1α and its target genes. Importantly, PS1-FAD mutations decreased PS1's ability to enhance PGC-1α mRNA levels. Analyzing the effect of APP and its γ-secretase-derived cleavage products Aβ and AICD on PGC-1α expression showed that APP and AICD increase PGC-1α expression. Accordingly, PGC-1α mRNA levels in cells deficient in APP/APLP2 or expressing APP lacking its last 15 amino acids were lower than in control cells, and treatment with AICD, but not with Aβ, enhanced PGC-1α mRNA levels in these and PSs-deficient cells. In addition, knockdown of the AICD-binding partner Fe65 reduced PGC-1α mRNA levels. Importantly, APP/AICD increases PGC-1α expression also in the mice brain. Our results therefore suggest that APP processing regulates mitochondrial function and that impairments in the newly discovered PS1/APP/AICD/PGC-1α pathway may lead to mitochondrial dysfunction and neurodegeneration.